The utility of the systemic immune inflammation and systemic inflammation response indices in suspected intermediate-risk pulmonary embolism - Uslu, Muhammed Fuad; Yilmaz, Mustafa; Ateşçelik, Metin; Atilgan, Feti Ahmet (Medicinska Naklada Zagreb, 2024)
Aim To evaluate the utility of the systemic immune inflammation index (SII) and systemic inflammation response index (SIRI) in diagnosing pulmonary embolism (PE) in emergency medicine. Methods We retrospectively reviewed the data of patients who presented to the emergency department and under-went contrast-enhanced computed tomography pulmonary angiography for suspected PE between January 1 and December 31, 2021. In 81/168 patients, the diagnosis of PE was confirmed and in 87/168 it was rejected. The data were analyzed with receiver operating characteristic analysis and binary logistic regression analysis. Results Patients with PE had a higher white blood cell count (P < 0.001), neutrophils (P = 0.002), monocytes (P = 0.013), neutrophil/lymphocyte ratio (P < 0.001), SII (P < 0.001), and SIRI (P < 0.001), and a lower lymphocyte count (P = 0.002). The SII had a sensitivity of 75.31% and a specificity of 71.26%, while the SIRI had a sensitivity of 82.72% and a specificity of 68.97%. Binary logistic regression analysis showed that the Wells score, D-dimer level, and SII independently influenced the diagnosis of PE. Conclusion The SII and SIRI may be used to support the diagnosis of PE in the emergency department. © 2024, Medicinska Naklada Zagreb. All rights reserved.
Keywords: Emergency Service, Hospital; Humans; Inflammation; Lymphocyte Count; Pulmonary Embolism; Retrospective Studies; D dimer; adult; aged; Article; computed tomography pulmonary angiography; contrast enhancement; controlled study; deep vein thrombosis; diagnostic test accuracy study; disease risk assessment; emergency ward; female; hemoptysis; human; human cell; immobilization; immune inflammation; inflammation; intermediate risk patient; leukocyte count; logistic regression analysis; lung embolism; lymphocyte count; major clinical study; male; malignant neoplasm; monocyte count; neutrophil count; neutrophil lymphocyte ratio; receiver operating characteristic; respiratory tract disease; retrospective study; sensitivity and specificity; systemic immune inflammation index; systemic inflammation; systemic inflammation response index; tachycardia; hospital emergency service; inflammation